The Influence Of Pregnancy Exercise On Normal Delivery Of Primiparous Mothers In 2023 - Hutabarat, Eva Nirwana Natalia; Ujung, Riance Mardiana; Simamora, Debora Lestari (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Pregnancy is a natural process that occurs in that the changes that occur in women during normal pregnancy are physiological in nature. The aim is to determine the effect of pregnancy exercise on the smooth delivery process of primiparous mothers at the BPM Suci Rahmadani Clinic. This research is a cross sectional study using an observational approach. The results of the study showed that of the 50% who participated in pregnancy exercise, 35.4% had normal deliveries, 14.6% had abnormal births. Of the 50% of mothers who did not participate in pregnancy exercise, 11.5% had normal deliveries and 38.5% had abnormal births. Based on the Odds Ratio (OR) value of 8.169, this means that mothers who do not exercise during pregnancy have a risk of abnormal labor of 8.169 times compared to mothers who exercise during pregnancy. It is recommended for mothers to take part in pregnancy exercise at least once a week so that the benefits of pregnancy exercise can be felt to the maximum. It is hoped that the Suci Rahmadani BPM Clinic will make pregnancy exercise one of the pregnancy care program policies, so that pregnant women can feel the benefits of the exercise. well.